2020
DOI: 10.3390/su12083383
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Complementary Direction of Guidelines for Developing Green Conventions in Korea: Using Comparative Analysis among Domestic and Overseas Cases

Abstract: As interests in sustainability have been increasing and discussions of environmental issues are ongoing globally, the MICE industry (Meeting, Incentive Travel, Convention, and Exhibition), which is attracting attention as a high value-added industry, also became an important part of the sustainability domain. Consequently, there has been a rise in hosting 'green conventions', or 'green MICE' which are designed to minimize all the negative impacts on the environment such as energy and water consumption. At some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 15 publications
1
3
0
2
Order By: Relevance
“…Among the five categories identified, event contents and capability, organizer and support/sponsorship, and impacts correspond to an event's own characteristics (internal factors), whereas facilities in venue and destination and the local event environment represent C&E-related facilities and infrastructure and a host destination's C&E environment (external factors). Such results reflect existing research by Kim et al [59] and Viale Pereira and Schuch de Azambuja [60] that highlight the importance of event planning and operations and confirm the findings of An et al [61] and Oh, Nam-Jo, and Kim [28], which demonstrated the importance of facilities, infrastructure, and local support as sustainable MICE factors. Particularly, in the current results, the top five indicators with the highest mean values were: (1) willingness of organizers (to hold succeessful C&E), (2) event differentiation strategy, (3) local support for hosting events, (4) cohesion between event theme with city-specific industry/image, and (5) clear (C&E) objectives.…”
Section: Discussionsupporting
confidence: 90%
“…Among the five categories identified, event contents and capability, organizer and support/sponsorship, and impacts correspond to an event's own characteristics (internal factors), whereas facilities in venue and destination and the local event environment represent C&E-related facilities and infrastructure and a host destination's C&E environment (external factors). Such results reflect existing research by Kim et al [59] and Viale Pereira and Schuch de Azambuja [60] that highlight the importance of event planning and operations and confirm the findings of An et al [61] and Oh, Nam-Jo, and Kim [28], which demonstrated the importance of facilities, infrastructure, and local support as sustainable MICE factors. Particularly, in the current results, the top five indicators with the highest mean values were: (1) willingness of organizers (to hold succeessful C&E), (2) event differentiation strategy, (3) local support for hosting events, (4) cohesion between event theme with city-specific industry/image, and (5) clear (C&E) objectives.…”
Section: Discussionsupporting
confidence: 90%
“…Hal tersebut sangat dapat dipahami mengingat bahwa pelaksanaan sebuah event MICE besar dalam skala internasional berpotensi untuk menghasilkan dampak lingkungan yang bersifat negatif secara signifikan (Kim, Moon, Chu, & Yoon, 2020). Dampak negatif yang paling sering disebut adalah seperti emisi gas rumah kaca, konsumsi air dan energi yang berlebihan, serta limbah sampah dari pelaksanaan event tersebut (Hou & Wu, 2021).…”
Section: Pendahuluanunclassified
“…Dalam konteks MICE, sustainable meeting adalah pelaksanaan meeting yang memasukkan pertimbangan lingkungan di semua tahapan, dimana hal tersebut bertujuan untuk meminimalkan dampak negatif pelaksanaan meeting pada lingkungan (Kim et al, 2020).…”
Section: Pendahuluanunclassified
“…The perceptions of employees have taken the driving seat when it comes to inducing commitment or engagement from them on organizational goals (Pimenta and Ball, 2015). An analysis of multiple hospitality and tourism companies revealed that the organizations with the most emphasis on environmental concerns asked their employees to engage in such practices too (Rahman et al , 2012; Kim et al , 2020). Similarly, Chou et al (2012) and Rawashdeh and Al-Ababneh (2021) stated that the encouragement of employees through management support helps them commit to pro-environmental behaviors.…”
Section: Literature Reviewmentioning
confidence: 99%